2016
DOI: 10.1103/physrevfluids.1.014401
|View full text |Cite
|
Sign up to set email alerts
|

Quasisteady quasihomogeneous description of the scale interactions in near-wall turbulence

Abstract: By introducing a notion of an ideal large-scale filter, a formal statement is given of the hypothesis of the quasi-steady quasi-homogeneous nature of the interaction between the large and small scales in the near-wall part of turbulent flows. This made the derivations easier and more rigorous.A method is proposed to find the optimal large-scale filter by multi-objective optimization, with the first objective being a large correlation between large-scale fluctuations near the wall and in the layer at a certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 32 publications
5
83
2
Order By: Relevance
“…The comparisons are shown in figure 2. The agreement for α is very good, while γ 1 discrepancy is of the order of 10%, which is also the degree of discrepancy reported in Zhang and Chernyshenko (2016) for other comparisons. While, obviously, at least a part of this 10% can be due to the truncation of the Taylor expansion, the QSQH theory itself is approximate only, as we will discuss in section 3.…”
Section: Qsqh Theorysupporting
confidence: 78%
See 3 more Smart Citations
“…The comparisons are shown in figure 2. The agreement for α is very good, while γ 1 discrepancy is of the order of 10%, which is also the degree of discrepancy reported in Zhang and Chernyshenko (2016) for other comparisons. While, obviously, at least a part of this 10% can be due to the truncation of the Taylor expansion, the QSQH theory itself is approximate only, as we will discuss in section 3.…”
Section: Qsqh Theorysupporting
confidence: 78%
“…For example, in (4) the amplitude modulation contribution to α is proportional to U(y) and the scale modulation contribution is proportional to y U y d d , which means that their ratio tends to unity as the wall is approached. For 1 g the scale-modulation mechanism is responsible for the section with negative slope of γ 1 (y), where this mechanism overcomes the contribution of the amplitude modulation (see figure 11 and the related discussion in Zhang and Chernyshenko (2016)). Therefore, any considerations based on the QSQH theory should always take into account the scale modulation element of the theory.…”
Section: Qsqh Theorymentioning
confidence: 95%
See 2 more Smart Citations
“…That study demonstrated that the turbulence statistics of the near-wall small scales remained universal, in the above sense, only up to y + ≈ 30-50, depending on the turbulence correlation in question. Contemporaneously, Chernyshenko et al [42], Zhang & Chernyshenko [43] developed a theoretical "Quasi-Steady -Quasi Homo- . geneous" (QSQH) framework that rests on the quasi-steady hypothesis, assumes the universality of the small-scale motion when scaled by the large-scale shearstress footprints, and configured to predict the response of near-wall turbulence to the Reynolds-number dependent large-scale outer motions.…”
Section: Quasi-steady Behaviourmentioning
confidence: 99%